Analisis Kesesuaian Wisata dan Daya Dukung Kawasan di Pantai Karang Bolong, Kabupaten Serang - Dinar Sartika; Agung Setyo Sasongko; Ferry Dwi Cahyadi (Faculty of Science and Technology University Ibrahimy, 2024)
Karang Bolong Beach which is located in Karang Suraga Village, Cinangka District, Serang Regency, Banten Province, has its own characteristics, namely there is a large hollow rock that forms like a gate which is a special attraction because other beaches do not have it. However, in the concept of sustainable ecotourism, a tourist attraction no longer only prioritizes the attractiveness of uniqueness, but the potential of ecotourism needs to be analyzed using a tourism suitability index and carrying capacity. The purpose of this study is to determine the level of suitability of tourism and the carrying capacity of the area as seen from oceanographic conditions and the aquatic environment. Data collection was carried out by means of field observations to observe and measure the parameters of oceanographic conditions and the aquatic environment at three observation stations which were determined using a purposive sampling technique. The results of the tourism suitability analysis at station 1 were 75% with the S2 category or suitable, at station 2 it was 80.95% with the S1 category or very suitable, and at station 3 it was 79.76% with the S2 category or suitable. The results of the carrying capacity of the Karang Bolong Beach area which has an area of ​​20,000 m² can accommodate as many as 1,200 visitors/day without causing ecological disturbance.